DAMPAK PSIKOLOGI MAKIAN BAHASA INDONESIA DITINJAU DARI STRATA SOSIAL MASYARAKAT BAHASA - Arfan Rauf (JURNAL KONFIKS, 2017)
This study was an observational research that starts from planning, implementing, and drawing conclusions. The research subjects were people who lived in Tamalatea Village, Makassar City, South Sulawesi, based on Social strata as many as 15 people. Data collection techniques were observation, tapping, fishing line, see, note, and record. All data obtained were analyzed through stages (1) grouping similar data, (2) reading the data as a whole, (3) analyzing data with the method of "intra-lingual and equivalent extra lingual methods", (4) compiling interpretations, and (5) describing data to be a conclusion.The results of the study showed that (1) invective is not acceptable in the form of language communication in general. (2) Invective can be accepted in certain language groups. (3) Invective is used to intimidate, control, reveal disappointment, wonder, personal protection, disrupt, and popularity. (4) There are similarities and differences in the use of invective in each of the social strata of the language community, both based on the form and reference, purpose, and character displayed. (5) Invective psychologically has negative impact on users and recipients.